Forging the Future: Aisyiyah's Trailblazing Role in Indonesian Early Childhood Education - Siswantari, Siswantari; Rahman, Syahidah Sumayyah; Abdurakhman, Abdurakhman (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2025)
This research examines the transformative journey of Aisyiyah, a prominent Indonesian women's organization dedicated to advancing early childhood education in Indonesia. The study critically assesses the profound impact of Aisyiyah on the evolution of early childhood education in Indonesia, spanning from the 20th century to the contemporary era. Within this historical context, access to education for indigenous populations, especially early childhood education, was notably restricted. However, Aisyiyah achieved a remarkable milestone by establishing the pioneering indigenous-owned kindergarten in Indonesia, Taman Kanak-Kanak Busthanul Athfal. As the organization expanded its presence, a growing network of kindergartens emerged despite the challenges posed by limited teaching resources and physical space. This research elucidates the dynamic growth of Aisyiyah's kindergarten network, demonstrating how the organization's commitment to early childhood education steadily intensified. Despite the initial absence of a standardized curriculum, the organization's branches increased annually. Over time, curriculum development and teaching methodologies underwent significant transformations, culminating in the selection of Taman Kanak-Kanak Busthanul Athfal as a pilot institution for kindergarten education in Indonesia. This study underscores Aisyiyah's pioneering role in developing early childhood education in Indonesia, emphasizing its tireless efforts to foster indigenous educational initiatives. By meticulously tracing Aisyiyah's contributions, this research provides valuable insights into the organization's pivotal role in shaping early childhood education in Indonesia.